The Association of Body Fat Percentage With Hypertension in a Chinese Rural Population: The Henan Rural Cohort Study - Li, Ruiying; Tian, Zhongyan; Wang, Yanhua; Liu, Xiaotian; Tu, Runqi; Wang, Yan; Dong, Xiaokang; Wang, Yikang; Wei, Dandan; Tian, Huiling; Mao, Zhenxing; Li, Linlin; et al. (Frontiers in Public Health, 2020)
Background: Obesity is an important risk factor for hypertension. Previous studies have explored the association between body fat percentage (BFP) and hypertension, but evidence on the consistency of the association remains uncertain and limited. The aim of this study was to explore the relationship between BFP and hypertension in a Chinese rural population. Methods: The present cross-sectional study including 38,913 eligible individuals was conducted in rural areas of Henan province. BFP was measured by bioelectrical impendence methods using Omron body fat and weight measurement device. Logistic regression models and restricted cubic spline regression models were performed to investigate the relationship between BFP and hypertension. Receiver operating characteristic (ROC) analyses were used to compare the discriminating power of adiposity indices. Results: The age-standard prevalence of hypertension was 23.74% and 17.87% in males and females, respectively. Compared with the first quartile of BFP, the adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for hypertension in the highest BFP quartile were 3.30 (95% CI: 2.85, 3.83) in males and 2.66 (95% CI: 2.36, 2.99) in females, and the adjusted ORs increased along with increasing BFP levels. The areas under ROC and 95% CIs of BFP were 0.673 (0.665, 0.682) in males and 0.696 (0.689, 0.703) in females, respectively. Conclusions: BFP was significantly positively associated with the prevalence of hypertension in both males and females in the Chinese rural population. Controlling of body fat should be emphasized in rural areas of China. Clinical Trial Registration: Registration number: ChiCTR-OOC-15006699. http://www.chictr.org.cn/showproj.aspx?proj=11375 Keywords: Hypertension, Body fat percentage, Dose-response relationship, Prevalence, Chinese rural population.